2015
DOI: 10.1002/2015jc011130
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, vertical structures, and heat/salt transports of mesoscale eddies in the southeastern tropical Indian Ocean

Abstract: Satellite altimetry sea surface height measurements reveal high mesoscale eddy activity in the southeastern tropical Indian Ocean (SETIO). In this study, the characteristics of mesoscale eddies in the SETIO are investigated by analyzing 564 cyclonic eddy (CE) tracks and 695 anticyclonic eddy (AE) tracks identified from a new version of satellite altimetry data with a daily temporal resolution. The mean radius, lifespan, propagation speed, and distance of CEs (AEs) are 149 (153) km, 50 (46) days, 15.3 (16.6) cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
90
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(100 citation statements)
references
References 74 publications
(149 reference statements)
7
90
3
Order By: Relevance
“…Initially designed for large‐scale climate studies (Riser et al, ), the international Argo program, which consists of almost 3,800 autonomous Lagrangian profiling floats in January 2018, has recently been used to study oceanic mesoscale eddies in different parts of the world oceans (Chaigneau et al, ; Li et al, ; Yang et al, ; Zhang et al, ). These floats provide freely available temperature and salinity data from the surface to as deep as 2,000 m (Coriolis Project: http://coriolis.eu.org).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially designed for large‐scale climate studies (Riser et al, ), the international Argo program, which consists of almost 3,800 autonomous Lagrangian profiling floats in January 2018, has recently been used to study oceanic mesoscale eddies in different parts of the world oceans (Chaigneau et al, ; Li et al, ; Yang et al, ; Zhang et al, ). These floats provide freely available temperature and salinity data from the surface to as deep as 2,000 m (Coriolis Project: http://coriolis.eu.org).…”
Section: Methodsmentioning
confidence: 99%
“…For each profile, the Steric Dynamic Height Anomaly (SDHA) , h, was computed using a reference level at 1,500 dbar, following the definition by Gill and Niiler () and Tomczak and Godfrey (): h= 15000δρ dz where δρ is the density anomaly of the profile, relative to CARS09, and dz is the vertical grid resolution. 1,500 dbar has been commonly referenced as no‐motion in former studies in this region (Yang et al, ). For any co‐located Argo‐eddy profile, a dynamic height anomaly more significant in the subsurface compared to the surface layers, would be representative of subsurface maximum in velocities associated with the eddy, hence a subsurface‐intensified eddy.…”
Section: Methodsmentioning
confidence: 99%
“…The identification and tracking of each eddy in the study domain are obtained from the Archiving, Validation, and Interpretation of Satellite Oceanographic (AVISO), a multiple satellite‐merged SSHA data set. It merges the measurements of several satellite altimeters and results in a product of a Mercator spatial resolution of 1/3° × 1/3° and a 7 day temporal resolution over the period from January 1993 to August 2013 [ Ducet et al ., ; Yang et al ., ]. Considering only the balance between pressure gradient and Coriolis force, the surface geostrophic current anomalies can be derived from the geostrophic balance formula [ Liu et al ., ; Yang et al ., ]: (u,v)=gf(hy,hx).…”
Section: Methodsmentioning
confidence: 99%
“…Yang et al . [] showed the mean vertical structures of anomalous temperature, salinity, and geostrophic currents of composite eddies in the southeastern tropical Indian Ocean, by analyzing Argo profile data inside altimeter‐detected eddies. Their composite analysis showed that eddy‐modulated anomalies were mainly confined in the upper 300 m in their study area.…”
Section: Introductionmentioning
confidence: 99%
“…As a ubiquitous phenomenon in the ocean, eddies play an important role in the transport and distribution of heat, salt, energy (Bishop et al, ; Chelton et al, , ; Chen et al, ; Chen, Gan, et al, ; Chen, Wang, et al, ; Chu et al, ; Dong et al, ; Liu et al, ; Roemmich & Gilson, ; Stammer, ; Stammer et al, ; Volkov et al, ; Wang et al, ; Xu et al, ; Yang et al, ; Z. G. Zhang et al, ; Z. W. Zhang et al, ), and marine biological and chemical processes (e.g., Gaube et al, ; Gruber et al, ; Johnson & McTaggart, ; Kouketsu et al, ; Vaillancourt et al, ). Dong et al () suggest that the global oceanic eddy movement can significantly influence distribution of the heat and fresh water in the ocean.…”
Section: Introductionmentioning
confidence: 99%